Comparison of clinical features and laboratory findings of coronavirus disease 2019 and influenza A and B infections in children: a single-center study - Meraj Siddiqui; Ayşe Gültekingil; Oğuz Bakırcı; Nihal Uslu; Esra Baskın (The Korean Pediatric Society, 2021)
Background As the coronavirus disease 2019 (COVID-19) outbreak continues to evolve, it is crucially important for pediatricians to be aware of the differences in demographic and clinical features between COVID-19 and influenza A and B infections. Purpose This study analyzed and compared the clinical features and laboratory findings of COVID-19 and influenza A and B infections in children. Methods This retrospective study evaluated the medical data of 206 pediatric COVID-19 and 411 pediatric seasonal influenza A or B patients. Results COVID-19 patients were older than seasonal influenza patients (median [interquartile range], 7.75 [2-14] years vs. 4 [2-6] years). The frequency of fever and cough in COVID-19 patients was lower than that of seasonal influenza patients (80.6% vs. 94.4%, P<0.001 and 22.8 % vs. 71.5%, P<0.001, respectively). Ageusia (4.9%) and anosmia (3.4%) were present in only COVID-19 patients. Leukopenia, lymphopenia, and thrombocytopenia were encountered more frequently in influenza patients than in COVID-19 patients (22.1% vs. 8.5%, P=0.029; 17.6% vs. 5.6%, P=0.013; and 13.2% vs. 5.6%, P= 0.048, respectively). Both groups showed significantly elevated monocyte levels in the complete blood count (70.4% vs. 69.9%, P=0.511). Major chest x-ray findings in COVID-19 patients included mild diffuse ground-glass opacity and right lower lobe infiltrates. There were no statistically significant intergroup differences in hospitalization or mortality rates; however, the intensive care unit admission rate was higher among COVID-19 patients (2.4% vs. 0.5%, P=0.045). Conclusion In this study, pediatric COVID-19 patients showed a wide range of clinical presentations ranging from asymptomatic/mild to severe illness. We found no intergroup differences in hospitalization rates, oxygen requirements, or hospital length of stay; however, the intensive care unit admission rate was higher among COVID-19 patients.